2019
DOI: 10.3390/cryst9070337
|View full text |Cite
|
Sign up to set email alerts
|

Bi2Te3 Topological Insulator for Domain-Wall Dark Pulse Generation from Thulium-Doped Fiber Laser

Abstract: We have experimentally demonstrated domain-wall (DW) dark pulses from a thulium-doped fiber laser incorporating a topological insulator saturable absorber (SA). The bulk-structured Bi2Te3 was used as the SA, which was constructed on a fiber ferrule platform through the deposition of the Bi2Te3 mixed with distilled water. The DW dark pulses were generated from the thulium-doped fiber laser cavity with a dual wavelength at 1956 nm and 1958 nm. The dark pulse width and the repetition rate were measured as ~10.3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, a study demonstrated the generation of a portable nanosecond laser with exceptional stability, showcasing a relative standard deviation of the pulse energy of less than 0.2% [41]. Furthermore, insights into the diverse approaches for achieving stable dark pulse generation are provided through investigations conducted on various materials, including topological insulators [42], carbon nanotubes [12], and plasmonic metamaterials [43]. Therefore, the signal-to-noise ratio is quite comparable to this work.…”
Section: Nanosecond Dark Pulse Generationmentioning
confidence: 51%
“…Additionally, a study demonstrated the generation of a portable nanosecond laser with exceptional stability, showcasing a relative standard deviation of the pulse energy of less than 0.2% [41]. Furthermore, insights into the diverse approaches for achieving stable dark pulse generation are provided through investigations conducted on various materials, including topological insulators [42], carbon nanotubes [12], and plasmonic metamaterials [43]. Therefore, the signal-to-noise ratio is quite comparable to this work.…”
Section: Nanosecond Dark Pulse Generationmentioning
confidence: 51%
“…Bismuth chalcogenides as topological insulators (TI) and narrow gap semiconductors represent a vast playground for novel physics and applications in the fields of thermoectricity [1], spintronics [2], unusual superconductivity [3], photodetectors [4], optical coatings [5] etc. Possible existence of Majorana fermions [6,7] and potential use in faulttolerant quantum computing [8] draw a great interest in topological superconductors (TSC) [9].…”
Section: Introductionmentioning
confidence: 99%